Ultra-sensitive bioanalysis of the therapeutic peptide exenatide for accurate pharmacokinetic analyses at effective plasma concentrations utilizing UPLC-MS/MS - Max Sauter; Philipp Uhl; Jürgen Burhenne; Walter E. Haefeli (Elsevier, 2020)
Exenatide is the first approved glucagon-like peptide 1 receptor agonist subcutaneously or intramuscularly injected for the treatment of type 2 diabetes mellitus. Typical therapeutic plasma concentrations are in the low pg/mL range, therefore requiring ultra-sensitive quantification. To enable the accurate evaluation of pharmacokinetic studies, we established a UPLC-MS/MS assay with a lower limit of quantification (LLOQ) of 5 pg/mL (1.2 pM) using 200 μL of plasma, validated according to FDA's and EMA's pertinent guidelines. Exenatide was isolated from plasma with solid phase extraction utilizing anion-exchange sorbent. Quantification was performed with positive electrospray ionization tandem mass spectrometry in the selected reaction monitoring mode. The calibrated concentration range of 5-10,000 pg/mL was linear showing correlation coefficients >0.99. Interday and intraday accuracy ranged from 97.5% to 105.4% with corresponding precision of <10.9%. Accuracy at the LLOQ ranged from 93.0% to 102.5% with corresponding precision of <15.9%. Because of the validity of a 10-fold dilution QC (accuracy 111.2%), the assay is suitable for exenatide quantification up to 100,000 pg/mL. The ultra-sensitive assay's applicability was demonstrated by the quantification of exenatide plasma concentrations and pharmacokinetics after intravenous and nasal administration to beagle dogs.